Assessment of the state financial security level - Pavelko, Olha; Doroshenko, Olena; Lazaryshyna, Inna; Vashai, Yulia (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/019, 2021)
The article describes the methodical approaches to assessment of the state financial security level. Ukraine has been taken as an example. A set of indicators that determine the level of financial security of Ukraine has been analyzed. For the purpose of optimizing the list of indicators that are taken into account while determining the integrated financial security level of Ukraine, the elements of correlation analysis have been used. The development of correlation matrix made it possible to identify the level of interrelationship between financial security indicators. A lot of indicators, proposed by the Methodical guidelines on the calculation of the level of economic security of the state, are closely correlated with each other, enhancingthe overall effect of their dynamics on the integrated level of financial security. The need to neutralize them has been established. All things considered, suggestions for improvement the Methodical guidelines on the calculation of the level of economic security of the state, based on the optimization of the indicator numbers and taking into consideration the close correlations between them, have been proposed. Such indicators as: level of capitalization of listed companies to GDP; gross international reserves of Ukraine; the share of loans in foreign currency; ratio of liquid assets to short-term liabilities; level of GDP redistribution through consolidated budget; the difference between the interest rates on loans granted by deposit-taking corporations and interest rates on deposits attracted by deposit-taking institutions (except NBU) have been recommended for removal from the method of Ukraine’s financial security assessment. The changes of methodical approaches to the diagnosis of the state financial security level will allow us to obtain a relevant information base for the analysis of the state financial security and make appropriate decisions concerning neutralization of threats and strengthening of security.